Two standard flora of the lower reaches of the Lena River, as an indicator of the territory’s biodiversity - Nikolin Evgenii (EDP Sciences, 2021)
The standard flora method established the diversity of vascular plants in two areas of the lower reaches of the Lena River (North-East Asia), which is estimated at 232 (216 species, 1 notospecies, 11 subspecies and 4 varieties) – 241 (228 species, 11 subspecies and 2 varieties) taxon/km2.